Analisis Keefektifan Platform Digital dalam Pembelajaran di PTKIN Se-Provinsi Lampung - Hasanah, Uswatun; Hadi, Fais Nurul; Fajriansyah, Irham (Khalifa Journal of Islamic Education, 2021)
This study aims to determine the type of platform used by lecturers in learning and analyze the effectiveness of the platform as a learning media during the Covid-19 pandemic. This study uses a quantitative method with a survey type, the source of the data is taken by using a questionnaire to 143 respondents from two universities, namely Raden Intan Islamic State University of Lampung and Metro Lampung Islamic State Institute. The data were analyzed using SPSS 20 software with descriptive analysis. The results of the analysis show that there are eight platforms used by lecturers as digital-based learning media, namely Zoom Cloud Meeting, Whatsapp Group, Google Classroom, Youtube Channel, Google Meet, Google Form, Facebook, and Instagram. In addition, the results of the analysis generally show that the use of digital-based platforms in the learning process is less effective. Some of the issues discovered include lack of supporting facilities that make the learning is not optimal, lack of lecturers’ ability to manage digital-based learning, and lack of learning innovation that makes the integration of technology in learning is not achieved. The results of this study can certainly be a reference for both universities in making policies, especially regarding digital-based learning during the Covid-19 pandemic.